Determinants of Women's Education Level in West Java: Impact of Economic Conditions or Discriminative Policies? - Mulyati, Sri; Indraswari, Indraswari; Pratikto, Rulyusa (KnE Social Sciences, 2022)
Various studies have shown that poor households with economic disruption have to choose their priorities. In such circumstances, expenses on girls’ education tend to be sacrificed. On the other hand, the emergence of public policies which discriminate against women and minority groups threatens to reduce women’s educational participation due to the psychological pressure and stigma they experience in educational institutions. This phenomenon is part of the reason why women’s educational participation in Indonesia is lower than men. This research applied a mix of quantitative and qualitative methods to investigate and compare the impact of discriminative policies and economic conditions on women’s education. Quantitative methods were conducted using a panel data regression model, while qualitative methods were conducted through content analysis. This study’s results showed that: a) discriminative policies were barriers to women’s rights for education; b) discriminative policies and economic variables had a significant influence on women at primary education level (elementary-junior high school) and at secondary education level (senior high school); c) regional income and expenditure had a significant effect on women’s education at primary and secondary education levels, but had no effect at post-secondary (university) education level; and d) economic and discriminative policy variables had no effect on women’s education at post-secondary (university) level. Keywords: discriminatory policy, economy, women’s education level